The disposition of lidocaine during a 6-hour intravenous infusion to young foals - Ohmes, Cameon (Kansas State University, 2015)
Differences in pharmacokinetics and drug disposition exist between young and adult animals which become especially important for drugs with a narrow therapeutic index. While the pharmacokinetics and plasma concentrations of intravenous lidocaine have been studied in adult horses, determination of the disposition in foals is necessary before appropriate clinical use can be determined. This study examined the disposition of intravenous lidocaine in healthy (phase I) and hospitalized (phase II) foals. Phase I consisted of 6 healthy 4-10 week old foals administered a 6-hour intravenous lidocaine infusion. Phase II consisted of 8 hospitalized foals (2-136 days old) administered intravenous lidocaine. A bolus (1.3 mg/kg) of lidocaine was administered intravenously to all foals followed by a 50 µg/kg/min infusion. Plasma lidocaine and monoethylglycinexylidide (MEGX) concentrations were determined. In phase I, plasma lidocaine concentrations remained below the suggested adult target range of 1-2 µg/mL with MEGX concentrations approximately half that of the parent drug. Total body clearance of lidocaine was 72.2 ± 7.8 mL/min/kg, elimination half-life (t₁/₂) was 26.3 ± 3.7 min, peak concentration (C[subscript]m[subscript]a[subscript]x) was 0.79 ± 0.07 µg/mL, and the volume of distribution (V[subscript]d) was 1.8 ± 0.4 L/kg. The C[subscript]m[subscript]a[subscript]x for MEGX was 0.36 ± 0.11 µg/mL, t₁/₂ was 60 ± 6 min and time to peak concentration (T[subscript]m[subscript]a[subscript]x) was 279.6 ± 90.3 min. In phase II, the severely compromised foals that were eventually euthanized had the largest fluctuations in plasma lidocaine and MEGX concentrations; foals that were discharged from the hospital had plasma concentrations below the target adult range similar to foals in phase I. In conclusion, despite low plasma lidocaine concentrations, the clinical benefits observed in foals may be due to the presence of metabolites. Further research in a larger population of unhealthy foals is required before comprehensive dosing recommendations can be made.
Keywords: Lidocaine; Intravenous; Foal; Monoethylglycinexylidide; MEGX; Veterinary Medicine (0778)